The Study of Uses and Gratification Theory of TikTok as A Shopping Platform Seen from Buyers’ View - Mutiara, Praventyasari; Putri, Kinkin Yuliaty Subarsa (Journal of Digital Marketing and Communication, 2024)
Shopping is one of the economic activities enjoyed by most people. Interest in new items is always a long-anticipated part of shopping. The growth of global industry and the disappearance of national borders have made a lot of information about shopping centers available, particularly through an online shopping application called TikTok Shop. As a new application, TikTok Shop has attracted the attention of its users, resulting in many requests being made through TikTok Shop. Using a qualitative approach, researchers describe people's habits by interviewing them about their use of TikTok Shop and what aspects satisfy them when shopping on TikTok Shop. By employing qualitative methodology and interviews, the researchers aim to understand why people use TikTok Shop nowadays. The results show that TikTok Shop is considered to meet users' wants and needs, providing satisfaction through discounts, live shows, and other minor features described in this article. The conclusion is that shoppers are likely to increasingly turn to TikTok Shop over the next few years, making it a favorite shopping tool.